The management system of cognitive economics - Nikulina Irina; Khomenko Igor; Zaharov Stanislav; Nehoda Evgeniy (SHS Web of Conferences, 2016)
The article contains various definitions of cognitive economy. An economy based on knowledge, should be provided by a modernized management system, which allows solving the problems of modern organizations in their functioning and development. The modern control system can effectively influence the cognitive economy through the highlighted items at the levels of the organization, thereby forming a complex of facilities management. The knowledge economy relies on the laws of the globalization, different directions of development of science and practice of management, prediction of the future, as well as the changes taking place in today’s business environment. In such an environment of modern society business is seen as an experiment. Various theories and management concepts are developed and supplemented with the changes in the life of people, organizations, industries and countries. Knowledge management concepts and theories are needed for technology of managerial work. In the era of cognitive economy, a manager must have the ability to use existing knowledge of management innovations applied to a particular situation, as well as to select areas of knowledge application for the development of the organization.